Hasil Belajar Matematika dengan Strategi Discovery Learning dan Group Investigation Ditinjau dari Keaktifan Siswa SMP - Sutama Sutama; Atik Mayasri (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2016)
The aim of observation is to analyses the effects of using learning strategies of investigation group and discovery learning base on the result of learning mathematic process, to analyses the effects of being active of students base on the result of learning mathematic process, to analyses of interaction between learning strategies of investigation group and discovery learning with being active on result of learning mathematic. The types base on scientific quantitative. Design of observation is quasi experimental. The technique of analysis data is using analysis variants two ways. Base on the result of observation, can conclude there are influence of strategies of group investigation and discovery learning for the result of learning mathematic with significant level 5%, to influence the level of being active in result of learning mathematic with significant level 5%, for the interaction between group investigation and discovery learning with significant level 5%.